Eyes in the sky, smart techs on the ground - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Unmanned aerial systems (UAS) – or drone-based technologies – have the potential to transform smallholder farming and help increase crop production. As a tool of precision agriculture, UAS provide farmers with realtime, actionable data on their land, crops and livestock, and help maximise input efficiency, minimise environmental impacts, optimise produce quality, and minimise risks. CTA is assisting African start-ups in acquiring the capacity to deliver UAS services to smallholders, under the project Transforming Africa’s agriculture; eyes in the sky, smart techs on the ground.